Pengaruh Variasi Pelarut Kulit Buah Manggis Terhadap Stabilitas Kertas Indikator Asam Basa Alternatif - Ernawati, Devi; , Triastuti Rahayu, M.Si (2017)
THE INFLUENCE VARIATIONS OF SOLUTIONS MANGOSTEEN RIND TO STABILITY PAPER ALTERNATIVE ACID BASE INDICATOR Abstract The acid base indicator is a material used to identify acid and base properties of a solution, it indicated by different color changes. The previous research show that anthocyanin content extracted from plants using filter paper can be reserve as a natural base acid indicator paper that is easy and practicaly to use. Based previous research mangosteen rind (Garcinia mangostana Linn) has a high antocyanin content of 59.3 grams / 100 grams of mangosteen rind. The objective of this research is to know the influence of solvent type on the color change of acid base indicator paper and the effect of storage duration on the color stability produced by acid base paper from mangosteen rind. This study used a complete randomized design (CRD) method with two factors: solvent type (95% ethanol and 95% ethanol + 1% HCl) and storage duration (0, 5, 10 and 15 days). The parameter of this research is the change of color of acid base indicator from the mangosteen rind after tested against strong acid base and weak base acid solution. Based on the results of the research, the basic acid indicator paper from the mangosteen rind in acid solution is red to orange and green in base solution. The best characteristic has shown by the acid base indicator paper with 95% ethanol solvent + 1% HCl because it has the best color sharpness, it is more stable and after 15 days storage can be used.